Deixis in The Novel The Kite Runner By Khaled Hosseini - Waladdin Panggabean; Khusnul Khatimah (Universitas Muhammadiyah Kalimantan Timur, 2022)
This research aims to identify the types of deixis used in the utterances in the novel The Kite Runner. The method used in this research is qualitative descriptive method because the data were analysed in the form of words and utterances. The data were taken from the utterances which is uttered by the characters in the novel. The theory used in this research is Deixis theory by Stephen C. Levinson’s, the result of this research shows that there are five types of deixis found in the novel The Kite Runner by Khaled Hosseini, those are: person deixis, place deixis, time deixis, discourse deixis, and social deixis. Based on the data deixis that have been found and analysed by the researcher in this research, person deixis is more dominant used in the novel.